Factors Explaining Language Performance After Training in Elders With and Without Subjective Cognitive Decline - López-Higes, Ramón; Prados, Jose M.; Rubio-Valdehita, Susana; Rodríguez-Rojo, Inmaculada; de Frutos-Lucas, Jaisalmer; Montenegro, Mercedes; Montejo, Pedro; Prada, David; Losada, María L. D. (Frontiers in Aging Neuroscience, 2018)
The present study explores if cognitive reserve, executive functions, and working memory capacity are predictive of performance in the language domain (specifically in sentence comprehension and naming) after a cognitive training intervention. Sixty-six Spanish older adults voluntarily participated in the study, classified either as older adults with subjective cognitive decline according to Jessen et al.’s criteria (n = 35; 70.94 ± 4.16 years old) or cognitively intact (n = 31; 71.34 ± 4.96 years old). Written sentence comprehension and visual confrontation naming were assessed both immediately after recruitment (at the baseline), and then six months later, once each participant had completed his/her cognitive training (a well-known program in Spain, called UMAM; English translation: Madrid City Council Memory Unit Program). Cognitive reserve, executive functions (cognitive flexibility and controlled interference efficiency), and working memory capacity were measured for all participants at the baseline. Results pointed out that the subjective cognitive decline group presented greater benefits in the language domain than cognitively intact participants. We also observed that lower executive functioning and working memory capacity at the baseline predicted larger benefits in language performance after training, but only in the group of cognitively intact older adults. However, selected predictors hardly explain subjective cognitive decline participant’s results in language performance after training.